Adaptations of cognitive remediation therapy for adolescents with anorexia nervosa for delivery via telehealth. Issue 1 (19th November 2022) - Orloff, Natalia C.; McGinley, Kate; Lenz, Katrina; Mack, Amy S.; Timko, C. Alix
Abstract: Objective: The COVID‐19 pandemic hastened a transition to treatment delivery via telehealth. While barriers still exist, the increased uptake of telehealth has the potential to increase access to mental health treatment for all diagnoses, including eating disorders. Delivery of evidence‐based treatment as well as adjunctive treatments, including those that are hard to find in‐person, have been modified to virtual format to increase accessibility and allow for continuity of care for adolescents with anorexia nervosa. Method: We describe how to modify and deliver Cognitive Remediation Therapy for youth with anorexia nervosa (CRT‐AN) via a telehealth platform. Preliminary and practical guidance for best practice for both group and individual delivery is established. Results: With minimal modifications, CRT‐AN can be delivered via telehealth for both individual and group delivery. More disengagement in group delivery was noted; however, overall application of the treatment via a remote platform was observed. Discussion: As more treatment moves to a telehealth format, highlighting how an adjunctive treatment like CRT‐AN can combined with other treatments in a telehealth format has the potential to increase research in its implementation and furthermore increase its dissemination. Public Significance: Cognitive Remediation Therapy for Anorexia Nervosa (CRT‐AN) requires significant manipulation of materials and supplementary human guidance. Suggestions for how to modify CRT‐AN for remote delivery via telehealth are provided. Modifications grew out of immediate changes made during the beginning of the COVID‐19 pandemic and can be used to inform changes therapists and programs can make to continue to or begin to use CRT‐AN in a remote fashion.